Cultivo de protoplastos de yuca y Stylosanthes - Szabados, Laszlo (International Center for Tropical Agriculture, 1985)
Methods of isolation and culture of cassava and Stylosanthes protoplasts are described. The application of these methods requires the routine regeneration of plants from isolated protoplasts. In cassava, protoplast isolation from leaves and shoot tips of plants cultured in vitro and from somatic embryos, differentiated from leaf segments, was possible with an enzyme mixture consisting of Onozuka cellulase, hemicellulase, and Pectolyase. Isolated protoplasts were purified by filtration and cultured in liquid medium; they regenerated cell wall after 1-2 days of culture and presented cell division after 3-4 days. Division frequency observed was 10- 20 percent in protoplast cultures from leaf mesophyll and shoot tips. In cultures of somatic embryos, this frequency was less than 5 percent. Within 3-4 wk., dividing protoplasts formed colonies. The plated colonies formed callus in several culture media. Protoplasts from 10 cassava var. have been isolated and cultured. (CIAT)